Information theory and coding by example - Kelbert, Mark; Suhov, Yuri (Cambridge : Cambridge University Press, 2013)
"Information Theory and Coding by Example" is a comprehensive textbook that introduces the fundamental principles of information theory and coding. The authors, Mark Kelbert and Yuri Suhov, draw from their extensive teaching experience to provide a clear and engaging presentation. The book covers both probabilistic and algebraic aspects of the subject, with a focus on practical applications. It includes a wide range of worked examples and exercises to reinforce understanding. The book is suitable for undergraduate and graduate students, as well as researchers and engineers seeking a solid foundation in information theory and coding.
Includes bibliography and index.
Keywords: Information theory; Probability theory; Coding theory; Entropy and information; Linear codes; Error correcting code; Cryptography; Quantum information theory